Profitability determinants of big European banks - Vesna Karadžić; Nikola alović (Journal of Central Banking Theory and Practice, 2021)
The subject of research in this paper is the profitability of the biggest banks in the European financial market, some of which operate in Montenegro. The profitability of banks is influenced by a large number of factors, including internal banking and external macroeconomic factors. The aim of this paper is to use statistical and econometric methods to examine which factors and with what intensity affect the profitability of large banks in Europe. The empirical analysis used highly balanced panel models with annual data on 47 large banks from 14 European countries over the period 2013-2018. Three static panel models were estimated and evaluated (pooled ordinary least squares, model with fixed effects and model with random effects), as well as dynamic model utilizing general methods of moments. The POLS model was chosen as the best, confirming that all macroeconomic factors have a statistically significant impact on the profitability of big banks, while the impact of internal factors, which are controlled by the bank's management, is not significant. GDP growth rate, inflation rate and market concentration have a positive effect on profitability, while the membership of the European Union has a negative impact on profit, meaning that banks with headquarters outside the EU are more profitable.
Keywords: C51; C52; C58; 330; bank profitability; big banks; macroeconomic variables; panel analysis; static models; GMM model